Simultaneous analysis of patin fish oil (Pangasius micronemus) and bandeng (Chanos chanos) fish oil using FTIR spectroscopy and chemometrics - Ikhsan, A. N.; Irnawati, I.; Lestari, L. A.; Erwanto, Y.; Rohman, A. (Rynnye Lyan Resources, 2022)
Patin fish (Pangasius micronemus) and bandeng fish (Chanos chanos) has high levels of oils containing essential fatty acids which are necessary for the human body. Therefore, quantitative analysis of fish oils extracted from patin fish and bandeng fish was very important. This research aimed to combine Fourier transform infrared (FTIR) spectroscopy with partial least square (PLS) and principal component regression (PCR) for simultaneous analysis of the binary mixture of patin fish oil (PFO) and bandeng fish oil (BFO). The method has consisted of extraction of both oils, preparation of calibration and validation samples, scanning of samples using FTIR spectrophotometer, and developing the calibration and validation models using PLS and PCR. The simultaneous analysis of PFO in a binary mixture with BFO was performed based on first derivative spectra at combined wavenumbers of 3050-2800, 1800-1700, and 1500-650 cm-1 assisted with PLS. In addition, BFO in binary mixtures with PFO was determined using the first derivative spectra using the same wavenumbers. The coefficient of determination for calibration (Rcal2) and validation (Rval2) were 0.9998 and 0.9994, with low errors (RMSEC = 0.0072 and RMSEP = 0.0121). The combination of FTIR spectroscopy with PLS using suitable wavenumbers can be potential tools for the simultaneous analysis of PFO and BFO. © 2022 The Authors. Published by Rynnye Lyan Resources.